Tingkat kompetensi kepribadian guru taman kanak-kanak - Husnia, Husnia; Permatasari, Sri Jumiaty; Fitriani, Wa Ode Heni (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
this research aims to determine the level of personality competence of kindergarten teachers. The research was conducted at Taman Kanak-Kanak Negeri Satu Atap Jati Desa Biru kecamatan Poleang Timur Kabupaten Bombana. This research is descriptive research using total sampling as a sampling technique. The total sample consisted of 10 teachers. Data was collected using a questionnaire technique which had previously gone through validity and reliability tests. The research data were then processed descriptively with percentage analysis. The research results show that the level of teacher personality competency is in the very good category. There needs to be further stimulus from related parties to ensure that this condition is maintained.